2017
DOI: 10.1002/eji.201646842
|View full text |Cite
|
Sign up to set email alerts
|

Mastering gut permeability: New roles for old friends

Abstract: Mast cells are innate immune cells that respond rapidly to infection in barrier tissues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…(2010) and our current study was that we used two parasites that physically overlap in their infection site (duodenum), whereas H. bakeri (duodenum) and E. falciformis (caecum) do not physically overlap. This suggests that in the case of coinfection of parasites that share the same niche, there is potential for more direct interaction between diverging immune cell populations as well as for tissue structural effects due to disruption of epithelial tissue integrity by the helminths (Boyett and Hsieh, 2014; Bramhall and Zaph, 2017). Specifically, in the case of H. polygyrus , tissue damage can occur when larvae are emerging from the gut epithelium and/or when feeding in the lumen as adults, which can limit the pool of suitable epithelial cells available for E. hungaryensis to infect.…”
Section: Discussionmentioning
confidence: 99%
“…(2010) and our current study was that we used two parasites that physically overlap in their infection site (duodenum), whereas H. bakeri (duodenum) and E. falciformis (caecum) do not physically overlap. This suggests that in the case of coinfection of parasites that share the same niche, there is potential for more direct interaction between diverging immune cell populations as well as for tissue structural effects due to disruption of epithelial tissue integrity by the helminths (Boyett and Hsieh, 2014; Bramhall and Zaph, 2017). Specifically, in the case of H. polygyrus , tissue damage can occur when larvae are emerging from the gut epithelium and/or when feeding in the lumen as adults, which can limit the pool of suitable epithelial cells available for E. hungaryensis to infect.…”
Section: Discussionmentioning
confidence: 99%
“…From the blood collected at 1.5 h post-challenge, we observed that mice treated with BLG-p(Man) had reduced levels of mMCPT-1 ( Figure 4 D), which is released by mucosal mast cells upon degranulation during allergic hypersensitivity responses. 33 , 34 IL-6 and IL-4 have been found to be elevated during anaphylaxis in patients with food allergies. 35 The mice treated with saline or free BLG also showed elevated IL-6 and IL-4 levels in the serum upon BLG challenge, but the mice treated with BLG-p(Man) did not ( Figure 4 D).…”
Section: Resultsmentioning
confidence: 99%
“…Histamine and mMCPT-1 are released from degranulating mast cells upon allergen cross-linking of IgE and are reliable markers of anaphylaxis. mMCPT-1 is a chmyase expressed by intestinal mucosal mast cells; elevated concentrations of mMCPT-1 increase intestinal barrier permeability during allergic hypersensitivity responses 46 , 47 . While ButM very effectively reduced the allergic response to peanut exposure, free NaBut had no effect in protecting allergic mice from an anaphylactic response (Fig.…”
Section: Resultsmentioning
confidence: 99%